2011
DOI: 10.1016/j.trstmh.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Wild, synanthropic and domestic hosts of Leishmania in an endemic area of cutaneous leishmaniasis in Minas Gerais State, Brazil

Abstract: Domestic, synanthropic and wild hosts of Leishmania spp. parasites were studied in an area endemic for American tegumentary leishmaniasis (ATL), specifically in northern Minas Gerais State, Brazil. Domestic dogs and small forest mammals are reservoir hosts for L. (Leishmania) infantum. However, the role that these animals play in the transmission cycle of the Leishmania spp. that cause cutaneous leishmaniasis is not well known. This study evaluated 72 rodents, 25 marsupials and 98 domestic dogs found in two vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 39 publications
4
53
1
14
Order By: Relevance
“…Here Quaresma et al [19] studied domestic and synanthropic wild hosts of L. braziliensis in an Indigenous Territory. Opossums were the second most frequent animal captured representing 19.6% of the total, 28.6% of which were infected with L. braziliensis.…”
Section: Didelphis In Brazilmentioning
confidence: 99%
See 2 more Smart Citations
“…Here Quaresma et al [19] studied domestic and synanthropic wild hosts of L. braziliensis in an Indigenous Territory. Opossums were the second most frequent animal captured representing 19.6% of the total, 28.6% of which were infected with L. braziliensis.…”
Section: Didelphis In Brazilmentioning
confidence: 99%
“…Marmosops incanus (Grey Slender Opossum) Quaresma et al [19] observed a prevalence of 50% (1/2) infection with L. guyanensis among M. incanus in one area in the state of Minas Gerais State where other animals, including rodents and canids, were infected with other Leishmania species, including L. braziliensis and L. infantum (Table 1). …”
Section: Marmosops In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural cases of infection have been observed in wild and synanthropic rodents, marsupials (BRANDÃO-FILHO et al, 2003;QUARESMA et al, 2011), cats (SCHUBACH et al, 2004), dogs (MADEIRA et al, 2006) and horses (AGUILAR et al, 1986). The role of animals in the transmission cycle is not fully understood; however, there is evidence that only wild rodents are reservoirs of L. (V.) brasiliensis (DANTAS-TORRES, 2007;MINISTÉRIO DA SAÚDE, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Existe una gran variedad de vectores pertenecientes a los géneros Phlebotomus y Lutzomyia en el viejo y nuevo mundo, respectivamente, capaces de transmitir el parásito y numerosos mamíferos que pueden actuar como reservorios, por tanto la situación epidemiológica es muy compleja (Laison 1983). En el control de esta parasitosis la vigilancia epidemiológica constituye una actividad fundamental para identificar variadas cadenas epidemiológicas compuestas por diferentes huéspedes mamíferos (Sabroza 2005, Quaresma et al 2011 y vectores transmisores (Perez-Doria et al 2008), datos elementales para la aplicación de eficientes planes de control. En el estudio epidemiológico de la Leishmania es indispensable conocer los reservorios domésticos y silvestres para poder analizar y determinar la forma en que se mantiene el agente etiológico en la naturaleza, como así también la manera de presentación de esta enfermedad en diferentes áreas geográficas y en sus distintas presentaciones clínicas.…”
Section: Introductionunclassified